Studies on Skeleton of Common Bronzeback Tree Snake(Dendrelaphis tristis) - Nagarajan, Hemavathi; Shanmugasundaram, Sivagnanam; Narayanasamy, Muniyappan; Sathik Basha , Sake Mohammed (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Dendrelaphis tristis is a non-venomous snake belongs to the Colubridae family. In this study a dead male Common Bronze Back tree snake was collected and skeleton was prepared for further study. The length of the body, skull, lower and upper jaw was measured as 795mm, 25mm, 32mm and 22mm respectively. The skeleton revealed a total of 314 vertebrae with a corresponding 163 pairs of ribs. Vertebral column was grouped as pre and post caudal region based on their anatomical variations. Cervical, first thoracic and post caudal group of vertebrae didn’t articulate with ribs. Sternum was absent and remnant of pectoral and pelvic girdle was not observed. Thus, this research will enhance the basic knowledge about the bones of Common Bronze Back tree snake for future conservational studies in the field of herpetology